2011
DOI: 10.1002/adsc.201100388
|View full text |Cite
|
Sign up to set email alerts
|

Copper‐Catalyzed Synthesis of Indole‐Fused Benzodiazepines[1]

Abstract: The copper-catalyzed synthesis of indolefused benzodiazepine via a cascade reaction between 3-halo-1H-indole-2-carbaldehydes and substituted 1,2-phenylenediamines is reported. Reactions

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…The other control experiment performed in the presence of CuI but absence of the ligand was also successful, but the yield of the product was relatively low (Table 1, Entry 17). In line with an observation made in our previous studies, [3] here too we found that the reaction with N-Boc-protected indoles produced Ndeprotected products in less time, but the yields were relatively low in comparison to the reaction with the unprotected indoles (compare Table 1, Entry 10 and Table 2, Entries 1-5). of Cs 2 CO 3 in DMSO under nitrogen).…”
Section: Studies Related To the Synthesis Of 2-amino-5hpyrimido[54-bsupporting
confidence: 92%
See 1 more Smart Citation
“…The other control experiment performed in the presence of CuI but absence of the ligand was also successful, but the yield of the product was relatively low (Table 1, Entry 17). In line with an observation made in our previous studies, [3] here too we found that the reaction with N-Boc-protected indoles produced Ndeprotected products in less time, but the yields were relatively low in comparison to the reaction with the unprotected indoles (compare Table 1, Entry 10 and Table 2, Entries 1-5). of Cs 2 CO 3 in DMSO under nitrogen).…”
Section: Studies Related To the Synthesis Of 2-amino-5hpyrimido[54-bsupporting
confidence: 92%
“…[1] Owing to their significant relevance, there is continued interest in the development of newer approaches to the syntheses of fused indoles. [3] More recently, we reported a facile and efficient synthesis of pyrazolo [4,3-d]pyrimidines through a copper-catalyzed cascade reaction between 4-iodopyrazole-3-carbaldehydes and substituted amidines. In an ongoing project in our lab, we have successfully employed substituted indole-2-carbaldehydes and their derivatives to such protocols to synthesize indole-fused pyridine, diazocine, quinoxaline, and benzodiazepine.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, a large number of methods, especially, various cyclizations, have been well developed after the first practical indole synthesis was reported by Fischer and Jourdan in 1883. 1,[4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] In particular, the introduction of transition metal reagents as catalysts (such as palladium, [19][20][21][22][23][24] gold, 5,10,14,25-28 rhodium, [29][30][31][32] ruthenium, 27,31,[33][34][35][36] platinum, 37 copper 6,18,22,[38][39][40][41][42][43][44][45][46][47][48] ) has deeply improved on the synthesis of indole and its derivatives. Among them, the ring closing of 2-ethynylaniline derivatives or their precursors (such as 2-bromo-anilines), 5,[49][50][51...…”
Section: Introductionmentioning
confidence: 99%
“…Compound 1 was made in high yield from the precursor indole-2carboxaldehyde via reaction with NBS, followed by Nbenzylation with base and BnBr and then acetal formation with ethylene glycol and pTSA. 20 We began our screening by treating 1 and acetophenone (2) with catalytic Pd(dtbpf)Cl 2 21 and NaOtBu in THF (Table 1), which are conditions previously used for related arylations in our laboratory, 16 and they afforded product 3 in an encouraging 52 % yield (entry 1). Pleasingly, compound 3 could be isolated in 93 % yield when the NaOtBu base was replaced by LiHMDS (entry 2).…”
mentioning
confidence: 99%
“…) 3 C); 13 C NMR (100 MHz, CDCl 3 ) δ C : 159.0, 141.8, 136.7, 135.0 (4 × C Ar ), 130.8 (C(1)), 129.3 (C Ar ), 128.9, 128.2, 127.8, 126.7, 121.8 (5 × HC Ar ), 121.6 (C Ar ), 119.6, 109.6 (2 × H Ar ), 109.4 ((4)), 47.1 (PhCH 2 N), 37.2 ((CH 3 ) 3 C), 30.9 ((CH 3 ) 3 C).9-Benzyl-4-isopropyl-3-phenyl-9H-pyrido[3,4-b]indole(20). This compound was prepared according to general procedure D, affording 20 (84 mg, 73%) as a brown solid.Mp: 170 -171 o C. IR ν max (thin film) 3055, 3030, 2990, 2958, 2929, 2872, 1439, 741, 701 cm -1 .…”
mentioning
confidence: 99%